Depression, antidepressant use, and breast cancer incidence in the Sister Study cohort - Mary V. Díaz-Santana; Jihye Park; Molly Rogers; Katie M. O’Brien; Hazel B. Nichols; Aimee A. D’Aloisio; Deborah B. Bookwalter; Dale P. Sandler; Clarice R. Weinberg (Breast Cancer Research)
Abstract Background Depression could affect breast cancer risk; however, epidemiologic findings are mixed. We assessed the association of breast cancer risk with self-reported history of diagnosed depression and time-dependent antidepressant use. Methods We analyzed data from 45,746 women in the Sister Study cohort (2003–2009). Cox proportional hazard regression was used to estimate hazard ratios (HR) for breast cancer. Results During follow-up (mean = 11.7 years), 3,899 breast cancers were diagnosed. There was no association between history of diagnosed depression and risk of breast cancer (HR = 0.98, 95%CI = 0.91–1.06). However, antidepressant use was associated with reduced risk of breast cancer (HR = 0.92, 95%CI = 0.85–1.00). Comparison of antidepressant drug classes revealed a suggestion of an inverse association with selective serotonin reuptake inhibitors (SSRIs, HR = 0.90, 95%CI = 0.81–1.00). Reduction was stronger in those with BMI < 25 (HR = 0.72, 95%CI = 0.59–0.89). Conclusions Depression was not associated with breast cancer risk. We observed a suggestion of a reduction in risk associated with antidepressant use. The analysis evaluating the association by specific drug types, showed a suggestion of a reduction in breast cancer risk associated with use of SSRIs. The negative association with overall antidepressant use and SSRIs, was stronger in those with BMI < 25, which could reflect a dose effect. This was the first study to examine the association between depression, antidepressant use, and breast cancer risk in a large genetic-risk-enriched cohort.